(untitled) (Proceedings of Southern Federal University. Philology, 2016)
Smirnova Olga Mikhailovna – candidate of philology, associate professor of foreign literature dpt. Russian State Pedagogic University of A.I. Herzen. Abstract. The second half of XVIII – the beginning of the XIX century in European art is the time more obvious crisis of rationalist ideology and normative poetics, with the inability to reflect and admit the irrational aspects of reality and human psyche. Rationalism crisis causes activation of myth-creating potential of culture. Pathos of early Romanticism is largely determined by the intention to syncretism, similar to syncretism of mythological thinking; artistic expression tends towards universalism of natural myths. An example of this is the poetic mythology of the first English romantic W. Blake. Nomination actualizes the most important aspects of poetic mythology of Blake as the ideological and axiological models alternative to the system of artistic rationalism. Blake’s myth-making, based on tradition and a system developed by the philosophical knowledge, however, overcomes the discourse of analytic speculation, bringing to life the pre-reflexive, archaic layers of culture. Artistic consciousness of transition period rebuilds its own identity, appealing to the myths of creation; stable images and scenes of aesthetic categories. Romantic art aspires the role of a new mythology, where the only carrier of transcendental experience is an artist, a creative potency rooted in the reality of the creative imagination. Key words: name, causality, coherence, myth, myth-making, nomination, symbol, eschatology.